2017
DOI: 10.1016/j.ejogrb.2017.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation products’ levels and mechanical properties of vaginal tissue in pregnancy

Abstract: .Advanced glycation products' levels and mechanical properties of vaginal tissue in pregnancy.European Journal of Obstetrics and Gynecology and Reproductive Biology http://dx.doi.org/10. 1016/j.ejogrb.2017.04.037 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…One category involves the analysis of AGEs in food and the assessment of factors and mechanisms that affect AGE production in food, the bioavailability of AGEs in the diet, and the effects of AGE intake on health . The other category involves analyzing AGEs in vivo , ,,, exploring the possible pathogenesis of AGEs in vivo and in vivo AGE generation, metabolism, and clearance mechanisms, ,, and investigating the association of AGEs with disease progression ,, and methods to reduce the physiological impacts of AGEs. , Among the above types of studies on AGEs, the largest number of studies focus on the physiological effects of AGEs in vivo and related inhibition methods, ,, of which the most common research model involves investigating the biochemical characteristics of AGE–BSA and the inhibition of the physiological effects of AGE–BSA.…”
Section: Fundamental Knowledge Of Agesmentioning
confidence: 99%
See 3 more Smart Citations
“…One category involves the analysis of AGEs in food and the assessment of factors and mechanisms that affect AGE production in food, the bioavailability of AGEs in the diet, and the effects of AGE intake on health . The other category involves analyzing AGEs in vivo , ,,, exploring the possible pathogenesis of AGEs in vivo and in vivo AGE generation, metabolism, and clearance mechanisms, ,, and investigating the association of AGEs with disease progression ,, and methods to reduce the physiological impacts of AGEs. , Among the above types of studies on AGEs, the largest number of studies focus on the physiological effects of AGEs in vivo and related inhibition methods, ,, of which the most common research model involves investigating the biochemical characteristics of AGE–BSA and the inhibition of the physiological effects of AGE–BSA.…”
Section: Fundamental Knowledge Of Agesmentioning
confidence: 99%
“…As shown in Figure , through the physiological functions described above, in vivo AGEs enhance oxidative stress, affect immune balance, promote chronic inflammation, cause tissue damage, change the functional properties of tissue proteins, promote protein aggregation, and further induce the occurrence of numerous diseases or accelerate disease progression. , However, the differences in physiological effects induced by free AGEs and protein-bound AGEs have not yet been completely elucidated. The relationship of AGE structures and their bioactivities, the number of AGE residues, and the structures of glycated proteins with the biological activity of AGE protein adducts has not been clarified.…”
Section: Ages: a Threat Or Benefit To Human Health?mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been hypothesized that the connective tissue of women prone to SG undergoes an abnormal reaction to the physiological stretch during pregnancy and labor. Pregnancy, confers unique alterations to the mechanical properties of connective tissues in order to meet their physiological demands [ 11 ] Studies that demonstrated a slower than normal outgrowth of fibroblasts in the skin from SG and a reduced level of fibrillin, collagen and elastin support this hypothesis [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%